Perlindungan Hukum Terhadap Anak Sebagai Korban Kekerasan Seksual Dalam Lingkup Keluarga (Studi Kasus Di Wilayah Hukum Pengadilan Negeri Larantuka) - Hendrikus Hussien Ruron; Aksi Sinurat; Orpa Ganefo Manuain (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Sexual violence against children constitutes a serious violation of human rights and causes long-term physical, psychological, social, and economic impacts on victims. The state has an obligation to provide comprehensive legal protection, including recovery through restitution and compensation. This study aims to analyze the implementation of legal protection for child victims of sexual violence within the family in the jurisdiction of the Larantuka District Court, as well as to identify the inhibiting factors in the provision of restitution to victims. This research employs an empirical legal research method with a socio-juridical approach. Data were collected through in-depth interviews with a judge of the Larantuka District Court as a key informant, supported by literature review of relevant laws and regulations as well as court case documents. The results of the study indicate that legal protection for child victims of sexual violence has been implemented through preemptive, preventive, and repressive measures. These efforts include legal socialization, child-friendly examination procedures, legal and psychological assistance, the provision of safe houses, and the criminal prosecution of perpetrators. However, such legal protection has not yet provided comprehensive recovery, as the rights to restitution and compensation have not been optimally fulfilled. The main obstacles to the provision of restitution include formalistic legal and procedural requirements, the economic limitations of victims’ families, social and cultural pressures that regard sexual violence as a family disgrace, and weak institutional coordination and victim assistance mechanisms. This study concludes that there is a significant gap between legal regulations and their practical implementation, resulting in the failure to fully realize economic recovery and the legal rights of child victims of sexual violence. Therefore, strengthening inter-agency coordination, improving public legal literacy, and optimizing the role of victim assistance institutions are necessary to ensure that restitution is effectively implemented as a form of just and substantive legal protection for child victims.